Kegiatan Bermain Meniup Mainan Tiupan Terhadap Status Oksigenasi Balita Dengan Pneumonia - Ni Luh Kompyang Sulisnadewi; I Ketut Labir; I Nyoman Ribek (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2015)
This study aims to determine the effect of playing activity toys puffs to oxygenation status of children under five years old with pneumonia. This study used a pre-experimental design with pretest-posttest approach with 15 sample that taken with accidental sampling technique. There results shown significant differences oxygenation status (RR, HR and oxygen saturation) before and after play activities puffs (p value = 0.000). The results of this study can be applied in providing nursing care for children with disorders of oxygenation.